2.45 Ghz passive RFID tag antenna mounting on various platforms - Yussuf, Abubeker A.; Islam, Md. Rafiqul; Khan, Sheroz; Khalifa, Othman Omran; Alam, A. H. M. Zahirul (IIUM Press, 2011)
This chaptcr presents the design of Microwave RFID ug antenna. The lag ameDnaS are designed using the electromagnetic simulation software called CST for a passive RHO tag operaling in the Microwave frequency band. A microwave band ug antenna was designed and simulated for 2.45GHz. A high gain (5.842dB), a good impedance matching with the microchip (-30.0 dB Retum Loss) and a satisfactory read range performance (up to 5 m) was obtained. One approach of designing RFlO ug is thai the lag should be less sensilive to lhe various types of objects. The effects of obstacles on antenna's characterislics have been investigated by placing the tag amenna against a meullic, rubber, glass and wood surfaces. Simulation results show slighl variations which is within tolerance range